IBM SAN Volume Controller Model SV3 product guide for IBM Storage Virtualize 8.6 - Gucer, Vasfi; Herd, Jon; Lonzer, Hartmut (IBM Redbooks, 2024)
This IBM® Redpaper® Product Guide describes the IBM SAN Volume Controller model SV3 solution, which is a next-generation IBM SAN Volume Controller. Built with IBM Storage Virtualize software and part of the IBM Storage family, IBM SAN Volume Controller is an enterprise-class storage system. It helps organizations achieve better data economics by supporting the large-scale workloads that are critical to success. Data centers often contain a mix of storage systems. This situation can arise as a result of company mergers or as a deliberate acquisition strategy. Regardless of how they arise, mixed configurations add complexity to the data center. Different systems have different data services, which make it difficult to move data from one to another without updating automation. Different user interfaces increase the need for training and can make errors more likely. Different approaches to hybrid cloud complicate modernization strategies. Also, many different systems mean more silos of capacity, which can lead to inefficiency. To simplify the data center and to improve flexibility and efficiency in deploying storage, enterprises of all types and sizes turn to IBM SAN Volume Controller, which is built with IBM Spectrum Virtualize software. This software simplifies infrastructure and eliminates differences in management, function, and even hybrid cloud support. IBM SAN Volume Controller introduces a common approach to storage management, function, replication, and hybrid cloud that is independent of storage type. It is the key to modernizing and revitalizing your storage, but is as easy to understand. IBM SAN Volume Controller provides a rich set of software-defined storage (SDS) features that are delivered by IBM Storage Virtualize, including the following examples: Data reduction and deduplication Dynamic tiering Thin-provisioning Snapshots Cloning Replication and data copy services Data-at-rest encryption Cyber resilience Transparent Cloud Tiering IBM HyperSwap® including three-site replication for high availability (HA) This Redpaper applies to IBM Storage Virtualize V8.6.
Includes bibliographical references
Keywords: Storage area networks (Computer networks); IBM computers; Virtual storage (Computer science); Réseaux de stockage (Informatique); IBM (Ordinateurs); Ordinateurs; Mémoires virtuelles